Psychological effect of cervical cancer screening when changing primary screening method from cytology to high‐risk human papilloma virus testing. Issue 1 (4th January 2019) - Andreassen, Trude; Hansen, Bo T.; Engesæter, Birgit; Hashim, Dana; Støer, Nathalie C.; Tropé, Ameli; Moen, Kåre; Ursin, Giske; Weiderpass, Elisabete
Abstract : From 2015, Norway has implemented high‐risk human papilloma virus (hrHPV) testing in primary screening for cervical cancer. Women aged 34–69 years, living in four counties, have been pseudo‐randomly assigned (1:1 randomization) to either hrHPV testing every 5 years (followed by cytology if hrHPV is positive), or cytology testing every 3 years (followed by hrHPV testing if low‐grade cytology is detected). We compared anxiety and depression scores among participants by screening arm and results. In total, 1, 008 women answered a structured questionnaire that included the validated Patient Health Questionnaire‐4 (PHQ‐4). The Relative Risk Ratio (RRR) of mild vs . normal anxiety and depression scores, and moderate/severe vs . normal anxiety and depression scores, were estimated by multinomial logistic regression with 95% confidence intervals (95% CIs). Compared to women who were screened with cytology, women randomized to hrHPV testing were not more likely to have mild anxiety and depression scores (RRR 0.96, CI 0.70–1.31) nor more likely to have moderate/severe anxiety and depression scores (RRR 1.14, CI 0.65–2.02). Women with five different combinations of abnormal screening test results were not more likely to have mild or moderate/severe vs . normal anxiety and depression scores than women with normal screening results. The likelihood of having abnormal long‐term (4–24 months after the screening) anxiety or depression scores among women 34 years and older was not affected by screening method or screening results. The results of our study suggest that a change to hrHPV testing in primary screening would not increase psychological distress among participants. Abstract : What's new? Norway is one of the first countries to implement high‐risk human papilloma virus (hrHPV) testing in primary cervical‐cancer screening. Does this newer type of testing impact the emotional well‐being of patients? In this study, the authors found no significant difference in either anxiety or depression scores between the viral‐screening arm and standard cytology screening. These findings could be useful for other countries considering implementing hrHPV testing, and are reassuring for the ongoing implementation process in Norway.